Impacts of social isolation caused by COVID-19 on the behavior of dogs and cats (Research, Society and Development, 2023)
A series of changes occurred in human routine due to the COVID-19 pandemic (Sars-CoV-2) with the recommendation of social isolation. Therefore, dogs and cats stayed longer with their tutors. This research aimed to verify the implications of this situation in the behavior of these animals residing in Aracaju, Sergipe, Brazil. For this study, a closed character questionnaire was applied through the Google Forms platform and digitally disclosed. Objective questions about the off-site fulfillment of physiological needs, body condition and levels of restlessness, sadness, meowing/barking, hair loss, licking/biting, itch, biting/scratching objects and emotional neediness were asked. Among the presented alterations, emotional neediness had the highest average and sadness the lowest average, the animals continued to make their needs in the usual places and there was some weight gain. It is concluded that social isolation did not cause estress on the pets, but instead a greater affective exchange with their tutors.